Pemilihan Komponen Jaringan Distribusi Air Bersih dengan Metode Rekayasa Nilai pada Perumahan Sawojajar - Dyah Retno Purwatiningsih (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
PDAM is service company in supplying used water to people's hoeses. But demand of pipe increase dramatically while the number of people population increase sharply and inefficient networking of pipe distribution cause PDAM set up and down the pipe that need high costValue engineering is one problem solving to overcome this case with conditions that have recomended Steps of applied value engineering that can solve integrated contains 5 steps : information step, creative step, analysis step, developing step, and presentation step. Based on analysis result using value engineering study got a comparison between initial alternative design and advised alternative design. Appearance some alternatives here from nerwork of pipe networking function structure produce 729 alternatives from 3 elements : priemer pipe distribution, secondary pipe network, and tersiery pipe network Thus, analysis result of component alternatives of water pipe distribution is :I Advised alternative : Perlormance : 85,541, Value : 1,26I Beginninga lternative : Perlormance : '79,149, Value : 1,00